2019
DOI: 10.1126/scisignal.aaw9450
|View full text |Cite
|
Sign up to set email alerts
|

KRAS G12C inhibition produces a driver-limited state revealing collateral dependencies

Abstract: Inhibitors targeting KRASG12C, a mutant form of the guanosine triphosphatase (GTPase) KRAS, are a promising new class of oncogene-specific therapeutics for the treatment of tumors driven by the mutant protein. These inhibitors react with the mutant cysteine residue by binding covalently to the switch-II pocket (S-IIP) that is present only in the inactive guanosine diphosphate (GDP)–bound form of KRASG12C, sparing the wild-type protein. We used a genome-scale CRISPR interference (CRISPRi) functional genomics pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
104
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 61 publications
16
104
0
Order By: Relevance
“…Finally, CDK4/6i and SHP2i worked in combination with KRASi in multiple 3D cultures supporting recent studies that tested its potential in combination with MEKi (Haines et al, 2018;Mainardi et al, 2018;Ruess et al, 2018). Indeed, in vivo pre-clinical evaluation of CDK4/6i in combination with KRASi showed promising results (Lou et al, 2019). Overall, our 26 approach was able to predict useful combinations with KRASi and drugs targeting multiple pathways that will benefit from further evaluation in pre-clinical models.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Finally, CDK4/6i and SHP2i worked in combination with KRASi in multiple 3D cultures supporting recent studies that tested its potential in combination with MEKi (Haines et al, 2018;Mainardi et al, 2018;Ruess et al, 2018). Indeed, in vivo pre-clinical evaluation of CDK4/6i in combination with KRASi showed promising results (Lou et al, 2019). Overall, our 26 approach was able to predict useful combinations with KRASi and drugs targeting multiple pathways that will benefit from further evaluation in pre-clinical models.…”
Section: Discussionsupporting
confidence: 64%
“…Next, we selected the 15 top up and downregulated pathways at 24 h and 7 days and analyzed their temporal response ( Figure S1D To assess phosphorylation-dependent signaling pathways after KRASi, we performed a global quantitative phosphoproteomic analysis identifying 21,048 phospho-peptides (Table S3). KRASi induced minor differences in the 1 h and 4 h phosphoproteome ( Figure S3A that is preferentially phosphorylated and activated in KRAS mutant cells, showed a decrease in phosphorylation upon KRAS inhibition (Lou et al, 2019;Vallejo et al, 2017). To identify the overall response pattern, we performed gene ontology (GO) enrichment analysis (biological processes) at 24 h, which revealed inhibition in DNA replication and cell cycle consistent with a cytostatic response ( Figure S3E-F).…”
Section: Defining Mechanisms Of Adaptation To Krasi In Pdac By Quantimentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it has been empirically shown that co-targeting EGFR along with a G12C inhibitor can result in increased inhibition of the KRAS G12C mutant in lung cancer and pancreatic cancer cell lines (12,13,(23)(24)(25)(26). We desired to test this combination in our colorectal cancer cells.…”
Section: Egfr Inhibitorsmentioning
confidence: 99%